The relationship between preseason common screening tests to identify inter-limb asymmetries in high-level senior and professional soccer players - Santos, Fernando J.; Valido, Aníbal J.; Malcata, Inês S.; Ferreira, Cátia C.; Pessôa Filho, Dalton M. [UNESP]; Verardi, Carlos E. L. [UNESP]; Espada, Mário C. (MDPI, 2021)
This study sought to examine inter-limb asymmetries in common screening tests performed during preseason and to analyze the relationship between the performance in the different tests. Nineteen high-level senior and professional soccer players (age: 23.2 ± 3.1 years; height: 181 ± 0.06 cm; body mass: 75.2 ± 4.8 kg) performed several common screening tests during pre-season: Dorsiflexion lunge test (DLT); bent knee fall out test (BKFO); y-balance anterior test (YBT A); y-balance posterolateral test (YBT PL); Y-balance posteromedial test (YBT PM); Heel-rise test (HRT) and single leg hamstring bridge test (SLHBT). High levels of reliability (ICC > 0.88 and <0.94) were observed in all the studied variables. Inter-limb significant differences were observed in DLT and YBT PM test (p < 0.01) but YBT A, HRT and SLHBT presented trivial effect size (ES) (0.03; 0.07 and 0.13, respectively), contrary to DLT, BKFO and YBT PL, all with small ES (0.20; −0.23 and −0.22) and YBT PM, which revealed very large ES (2.91). Considering all data, high-level senior and professional soccer players present fairly good mean values of lower limb symmetry. Performance considering all tests was different, a fact associated with different biomechanical dynamics (e.g., YBT), nonetheless, the correlations between tests underline the relationship between these, which could represent important evidence to consider for injury prevention and performance enhancement programs.
Keywords: Biomechanical; Injury risk; Inter-limb; Performance; Soccer; Symmetry